Determination of Total Citronelal Levels and Development of FTIR-Chemometric Classification Model of Cymbopogon winterianus Jowitt Oil from Different Altitudes of Planting Areas - Jazila, Yusrin; Kristiningrum, Nia; Wulandari, Lestyo (Tropical Biopharmaca Research Center, IPB University, 2023)
Cymbopogon winterianus Jowitt oil (CWJ oil) is a vegetable oil with very wide uses in food sector, cosmetics, medicines and chemical industry. Citronelal compound is one of the quality requirements that determine the quality of CWJ oil. This study aims to develop a chemometric-FTIR classification model and to determine the total citronellal content of Cymbopogon winterianus Jowitt oil grown in low and medium lands. The sample used was citronella oil from Jember and Banyuwangi regions. The cleaned CWJ herbal samples were withered, chopped and distilled to produce CWJ oil. CWJ oil was scanned using FTIR spectroscopy and then the FTIR spectras were analyzed using LDA, SVM and SIMCA to form a CWJ oil classification model. The selected classification model was then validated using leave one out cross validation and external validation. The LDA classification model showed the best results with 100% accuracy of model recognition and validation. The results of the determination of total citronellal levels of CWJ oil using the hydroxylamine method showed that samples of CWJ oil from Banyuwangi had higher levels of total citronellal than samples from Jember. The average levels of total citronellal CWJ oil from Banyuwangi and Jember regions were 32.84%, and 26.06%, respectively.